2020
DOI: 10.1007/s42452-020-2188-3
|View full text |Cite
|
Sign up to set email alerts
|

Early hydration of C2S doped with combination of S and Li

Abstract: Production of low-energy cements would result in energy saving and lower CO 2 emissions related to reduced consumption of fuel and high-grade limestone as a raw material. Belite rich clinker, made more reactive by doping with combination of S and Li, could possibly be one of the low-energy alternatives for Portland cement clinker. Paper describes the preparation of doped belite and deals with its early hydration and reactivity. Belite rich clinkers were prepared in laboratory in high-temperature solid state sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The highly located LDOS of VBM around one oxygen type atoms in β-C 2 S indicates high reactivity under electrophilic attacks (Figure 2e), while the uniformly distributed LDOS of VBM could explain the non-reactivity to water of γ-C 2 S (Figure 2i) [23]. Such theoretical works attempted to introduce impurities to enhance the β-C 2 S reactivity rate with water [23,40]. Furthermore, DFT studies reported that C 3 A reactivity originates from O-2p, Ca-3p, Ca-3s and Al-3p orbitals, and that the LDOS of the VBM and the CBM are localized in the vicinity of oxygen atoms and calcium atoms respectively [41].…”
Section: General Reactivitymentioning
confidence: 99%
“…The highly located LDOS of VBM around one oxygen type atoms in β-C 2 S indicates high reactivity under electrophilic attacks (Figure 2e), while the uniformly distributed LDOS of VBM could explain the non-reactivity to water of γ-C 2 S (Figure 2i) [23]. Such theoretical works attempted to introduce impurities to enhance the β-C 2 S reactivity rate with water [23,40]. Furthermore, DFT studies reported that C 3 A reactivity originates from O-2p, Ca-3p, Ca-3s and Al-3p orbitals, and that the LDOS of the VBM and the CBM are localized in the vicinity of oxygen atoms and calcium atoms respectively [41].…”
Section: General Reactivitymentioning
confidence: 99%